2009
DOI: 10.1002/clc.20650
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Congenital Coronary Artery Fistulae: Immediate and Long‐Term Follow‐Up Results

Abstract: BackgroundTranscatheter closure of coronary artery fistulae (CAF) has emerged as an alternative to surgery, but there are no long‐term outcome results.ObjectiveWe report immediate and long‐term results in 24 patients after transcatheter closure of congen‐ ital CAF.MethodsA total of 24 patients aged 5 to 56 years old with congenital CAF underwent attempted percutaneous transcatheter closure using various devices between November 1998 and August 2008. The immediate closure results and clinical follow‐up were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 18 publications
(14 reference statements)
2
44
0
1
Order By: Relevance
“…Residual or recurrent shunts after transcatheter closure have been reported in 10-20% of patients and these may require further procedures to achieve complete occlusion. 24,26 A study shows that an incidence of major complications which occurs late after closure of CAFs with transcatheter and surgical interventions is 15%, reported by Valente et al 27 Mortality related to surgical closure or transcatheter closure of isolated CAFs is low (<1%) 20,28 In our study, CAF closure was attempted percutaneous occlusion in all the 5 cases & used three different devices; VAD occluder, PDA Occluder and detachable Cook coil to close the lesions. Among 5 patients, we approached percutaneous CAF closure though venous approach in 4 cases with and only one through arterial approach.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Residual or recurrent shunts after transcatheter closure have been reported in 10-20% of patients and these may require further procedures to achieve complete occlusion. 24,26 A study shows that an incidence of major complications which occurs late after closure of CAFs with transcatheter and surgical interventions is 15%, reported by Valente et al 27 Mortality related to surgical closure or transcatheter closure of isolated CAFs is low (<1%) 20,28 In our study, CAF closure was attempted percutaneous occlusion in all the 5 cases & used three different devices; VAD occluder, PDA Occluder and detachable Cook coil to close the lesions. Among 5 patients, we approached percutaneous CAF closure though venous approach in 4 cases with and only one through arterial approach.…”
Section: Discussionmentioning
confidence: 59%
“…None had follow-up angiograms. Recently, Zhu et al 24 reported transcatheter closure results of 24 patients. All had clinical follow-up ranging from 3 months to 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Various occlusion devices are available for the closure of the CAFs. These are Gianturco and polyester-covered stainless steel coils, detachable balloons, umbrella devices, covered stent polyvinyl alcohol particles, glue and a combination of these instruments (Tacoy et al, 2009;Zhu et al, 2010). The above mentioned coils are used primarily in smaller CAFs (Figure-8).…”
Section: Devicesmentioning
confidence: 99%
“…Compared with umbrella devices, the plug affords greater opportunity to close the tortuous fistulae as it can be delivered through a flexible guiding catheter. Detachable coils can also be delivered through a guiding catheter, however, it seems that the plug has advantages over the detachable coil in ease of delivery and incidence of residual flow (Zhu et al, 2010). Double umbrella devices allow more precise positioning and are used in larger fistulae with coronary branches close to the occlusion site ( Figure-9) (Armsby et al, 2002).…”
Section: Devicesmentioning
confidence: 99%
See 1 more Smart Citation